2013
DOI: 10.1111/pme.12158
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Pressure Pain Threshold in Healthy Chinese Men

Abstract: It is important for physicians and researchers to consider these variables when evaluating pain sensitivity in clinic and in research. The underling mechanisms between these factors and pressure pain perception are worthy of further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
4
42
1
Order By: Relevance
“…41,42 Moreover, this sensitivity could be influenced by many factors attributed to central or peripheral neurons and related to modulated pain pathways, as well as by other factors, such as demography, metabolism and lifestyle. [43][44][45][46] The involvement of the anterior temporalis, which had a significant correlation with neck disability, reinforces the concept of complex interconnections between masticatory and cervical structures. 47 Although this correlation was observed between neck disability and muscle sensitivity, no association with pain intensity was found, indicating that these parameters are a reflection of different aspects of the painful condition.…”
Section: Discussionsupporting
confidence: 60%
“…41,42 Moreover, this sensitivity could be influenced by many factors attributed to central or peripheral neurons and related to modulated pain pathways, as well as by other factors, such as demography, metabolism and lifestyle. [43][44][45][46] The involvement of the anterior temporalis, which had a significant correlation with neck disability, reinforces the concept of complex interconnections between masticatory and cervical structures. 47 Although this correlation was observed between neck disability and muscle sensitivity, no association with pain intensity was found, indicating that these parameters are a reflection of different aspects of the painful condition.…”
Section: Discussionsupporting
confidence: 60%
“…The subgroup of labourers from the metalworking industry revealed higher pain thresholds compared with the remaining sample. This finding is in line with a Chinese study (N = 2517), which reported higher pressure pain thresholds for "manual" labourers compared with "nonmanual" labourers (Zhang et al, 2013) and a study comparing six experienced butchers to a control group of twenty students (Madeleine, Lundager, Voigt, & Arendt-Nielsen, 2003). One possible explanation is that painful encounters seem more likely for "manual" labourers, which could lead to desensitization to painful stimuli (Rennefeld, Wiech, Schoell, Lorenz, & Bingel, 2010).…”
Section: Subject Factorssupporting
confidence: 88%
“…In addition to back pain [ 23 , 24 ], people who are obese are more prone to hyperuricemia and gout [ 25 ], and osteoarthritis [ 26 ]. In addition, body mass and pain threshold have been reported to be inversely related [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%